Broadband tunable hybrid photonic crystal-nanowire light emitter - Wilhelm, Christophe E. (2017)
We integrate about 100 single cadmium selenide semiconductor nanowires in silicon nitride photonic crystal cavities in a single processing run. Room temperature measurements reveal a single and narrow emission linewidth, corresponding to a Q-factor as large as 5000. By varying the structural parameters of the photonic crystal, the peak wavelength is changed, thereby covering the entire emission spectral range of the active material. A very large spectral range could be covered by heterogeneous integration of different active materials.